Tomatoes or cabbage for dinner? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Integrated Vegetable Pest Management. Safe and Sustainable Protection of Small-scale Brassicas and Tomatoes